2012
DOI: 10.1098/rsta.2011.0295
|View full text |Cite
|
Sign up to set email alerts
|

Development and recent evaluation of the MT_CKD model of continuum absorption

Abstract: Water vapour continuum absorption is an important contributor to the Earth's radiative cooling and energy balance. Here, we describe the development and status of the MT_CKD (Mlawer-Tobin-Clough-Kneizys-Davies) water vapour continuum absorption model. The perspective adopted in developing the MT_CKD model has been to constrain the model so that it is consistent with quality analyses of spectral atmospheric and laboratory measurements of the foreign and self continuum. For field measurements, only cases for whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
330
1
21

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 427 publications
(385 citation statements)
references
References 41 publications
5
330
1
21
Order By: Relevance
“…As was stressed earlier, the contribution from the water vapour self-continuum (H 2 O−H 2 O) and from N 2 −N 2 and O 2 −O 2 CIA was excluded from C f . The MTCKD-2.5 model [9,10] and the far-wings model of Tipping & Ma [8] are presented for comparison. Figure 5 shows in more detail the 4 mm (2500 cm −1 ) window.…”
Section: (B) Error Of the Derived Continuummentioning
confidence: 99%
See 2 more Smart Citations
“…As was stressed earlier, the contribution from the water vapour self-continuum (H 2 O−H 2 O) and from N 2 −N 2 and O 2 −O 2 CIA was excluded from C f . The MTCKD-2.5 model [9,10] and the far-wings model of Tipping & Ma [8] are presented for comparison. Figure 5 shows in more detail the 4 mm (2500 cm −1 ) window.…”
Section: (B) Error Of the Derived Continuummentioning
confidence: 99%
“…The sample measurements (step 3) were typically made in a mixture of 300-600 mbar water vapour, depending on temperature, and 4400-4700 mbar of air (table 1). The background measurements with an empty cell and with air were carried out, first, to ensure that any possible cell distortion due to pressure was taken into account and, [20], light grey lines) calculated up to 25 cm −1 from the line centres without a plinth; experimental RAL (dark grey lines) spectrum; MTCKD-2.5 (dashed lines) total continuum [9,10]; optical depth of the total (i.e. self plus foreign) continuum (dots) derived as a spectrally smoothed difference between RAL and UCL08 in microwindows between lines; contribution from the self-continuum (circles) derived using data [16] for the same temperature.…”
Section: Experimental Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…One spectral region subject to large changes recently in v. 2.5 is in the range 3-5 mm (2000-3200 cm −1 ) based on analysis of satellite-and ground-based infrared measurements [22]. Other work has previously suggested that past versions of MT_CKD underestimated the magnitude of the self continuum in this region [9].…”
Section: Resultsmentioning
confidence: 99%
“…This particularly covers models for the micro-and millimeter-wave region (e.g., Liebe et al, 1993;Rosenkranz, 1993Rosenkranz, , 1998 but also several editions of the Clough-Kneizys-Davies continuum model (CKD; Clough et al, 1989Clough et al, , 2005, later enhanced by Mlawer and Tobin (MT_CKD;Mlawer et al, 2012), models that cover the entire millimeter to infrared spectral range. However, all of these continua have been developed with a focus on Earth observations.…”
Section: Continuum Modelsmentioning
confidence: 99%